Massive GaN micro-LED array based underwater wireless optical communication - Lv, Zhijian; Liu, Xinyi; Wu, Shuang; Zhang, Wenwei; Yue, C. Patrick; Liu, Zhaojun (Optics express, 2025)
High-speed underwater wireless optical communication technology is a much-needed communication technology in current underwater applications, and micro-LED is a promising light source option. Considering the limitation of transmission distance due to the low optical power of a single micro-LED pixel, an underwater wireless optical communication system based on a novel massive GaN micro-LED array includes more than 5000 pixels fabricated via flip-chip technology is proposed, which can achieve 165-Mbps and 90-Mbps at 37.7 m and 73.5 m, respectively. Therefore, the feasibility of realizing a high data rate and long transmission distance in an underwater wireless optical communication system based on a novel massive micro-LED array is confirmed.